2011
DOI: 10.5146/tjpath.2011.01008
|View full text |Cite
|
Sign up to set email alerts
|

Profile of gallbladder diseases diagnosed at afyon kocatepe university: a retrospective study

Abstract: Objective: Superficial tumors including Ta, Tis, and T1 make up 75% of urothelial carcinomas of the bladder. While the behavior of these superficial urothelial cancers is relatively benign, invasive tumors have a significant mortality rate. However, Ta and T1 tumors might display different biological behavior. There is therefore a great need for biomarkers that can accurately distinguish the behavior of urothelial carcinomas in addition to tumor grade and stage. our aim was to determine the immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Among various gall stones, cholesterol stones, mixed stones and pigmented stones were commonly found. Mazlum M et al [12] reported that cholesterol stones were common in gallbladder lesions in urban population while in our study pigment stones were more commonly found comprising 51.03% cases. In the study of Rakesh B.H et al [8] and Bansal et al [7] the pigment stones were found in proportion of 60% and 38%.…”
Section: Discussionmentioning
confidence: 46%
“…Among various gall stones, cholesterol stones, mixed stones and pigmented stones were commonly found. Mazlum M et al [12] reported that cholesterol stones were common in gallbladder lesions in urban population while in our study pigment stones were more commonly found comprising 51.03% cases. In the study of Rakesh B.H et al [8] and Bansal et al [7] the pigment stones were found in proportion of 60% and 38%.…”
Section: Discussionmentioning
confidence: 46%